Clinicopathological study of benign breast diseases in Bundelkhand regions - Badigi Prashant Naik; Saurabh Purohit (Asian Journal of Medical Sciences, 2024)
Background: Benign breast diseases are a neglected entity despite the fact that it constitutes the majority of breast complaints and that the vast majority of the lesions that occur in the breast are benign. Aims and Objectives: The aims and objectives of the study are to analyze the percentage of incidence, age distribution, and other associated factors of benign breast diseases. Materials and Methods: The prospective study was conducted on 100 cases of benign breast diseases in Maharani Laxmi Bai Medical College, Jhansi, between January 2021 and June 2022. Results: Lump was found in all participants (100%) in which incidence of painless and painful lump was for 94% and 6%, respectively. 6% lump was found to be associated with non-cyclical mastalgia and 2% lump had having association with discharge. Milky discharge (1%) was found in the case of galactocele and serous discharge (1%) was found in duct ectasia. Benign breast diseases were found most commonly in premenopausal women (97%) in comparison to post-menopausal women (3%). Breast lump was investigated by fine needle aspiration cytology which was consistent with a lump of fibroadenoma and fibroadenosis in 95% of cases. Rest 5% of breast lumps were non-consistent. 90% of cases were found of fibroadenoma. All patients underwent surgical line of management except for fibroadenosis which was managed conservatively. Cases of breast abscess, fibroadenoma, duct ectasia, and galactocele admitted in hospital, for which mean hospital stay was 4.28 plus or minus 6.21 days. Conclusion: The most common benign breast disease encountered in clinical practice is fibroadenoma followed by fibroadenosis. They are most common in 15–25-year age group and its presentation is found to be more in married woman.